Determinants Impacting Efficacy of Organizational Blogs - Sharma, Rajesh; Jain, Kamal Kishore (Archives of Business Research, 2016)
Abstract: Recent revolution in the Information and Communication Technology has brought forth several tools for organizational learning and knowledge transfer. Organizational blogging has received considerable attention for its use for managed socialization leading to dialogue, reflection and knowledge transfer among the employees of large organizations. However this powerful tool of knowledge sharing can lead to adverse consequences in the absence of suitable checks in organizations. The paper uses the framework of interpersonal relationships proposed by Hon and Grunig to identify determinants that can impact efficacy of organizational blogs as a knowledge sharing tool. A case study of organizational blog of a leading service provider of India in the field of communication is presented for validating the findings from the literature. We suggest the possibility of using moderator to overcome the anticipated pitfalls in use of this popular medium of knowledge sharing in organizations.